2009
DOI: 10.1111/j.1476-5381.2009.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of a hydrogen sulphide donor (sodium sulphide) in an ovine model of burn‐ and smoke‐induced acute lung injury

Abstract: Background and purpose:The present study investigated whether the pathophysiological changes induced by burn and smoke inhalation are modulated by parenteral administration of Na2S, a H2S donor. Experimental approach: The study used a total of 16 chronically instrumented, adult female sheep. Na2S was administered 1 h post injury, as a bolus injection at a dose of 0.5 mg·kg -1 and subsequently, as a continuous infusion at a rate of 0.2 mg·kg -1 ·h -1 for 24 h. Cardiopulmonary variables (mean arterial and pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 56 publications
0
44
0
1
Order By: Relevance
“…We previously demonstrated that 3-NT, as an indirect measure of ONOO Ϫ formation, is markedly elevated in lung tissue of sheep subjected to combined burn and smoke inhalation injury (6,24,28,36). Formation of ONOO Ϫ may influence the inflammatory response to this injury at multiple levels.…”
Section: Discussionmentioning
confidence: 98%
“…We previously demonstrated that 3-NT, as an indirect measure of ONOO Ϫ formation, is markedly elevated in lung tissue of sheep subjected to combined burn and smoke inhalation injury (6,24,28,36). Formation of ONOO Ϫ may influence the inflammatory response to this injury at multiple levels.…”
Section: Discussionmentioning
confidence: 98%
“…For example: lethal hypoxia [3], ischemia/reperfusion (I/R)-injury [430], cardiac arrest [3136], hemorrhage and resuscitation [3745], acute lung injury resulting from blunt chest trauma [46,47] and/or injurious mechanical ventilation [4850], as well as systemic inflammation resulting from endotoxin injection [5159], acute pancreatitis [6063], polymicrobial sepsis [6470], and/or burn injury [7173]. While the beneficial effect of exogenous H 2 S supplementation and maintaining endogenous H 2 S production, respectively, are well-established in I/R injury, equivocal results were reported after cardiac arrest, hemorrhage and resuscitation, and, in particular, in sepsis: inhaling gaseous H 2 S [33,44,48,50,53,54,65], the injection of the sulfide-containing salts NaSH [31,39,49,51,59,63,64,6671,120] and Na 2 S [32,3438,41,42,44,47,48,72,73] or the slow-releasing H 2 S donor GYY4137 [55] as well as of inhibitors of H 2 S production [43,45,5860,62,63,6771,120] were associated with attenuation of shock-related organ dysfunction. Consequently, knowledge about vascular sulfide concentrations may assume major importance, in particular in the context of “ acute on chronic disease ”, i.e., during circulatory shock in animals with pre-existing chronic disease, which per se may markedly alter endogenous H 2 S production, e.g., atherosclerosis [74], arterial hypertension [75,76], chronic kidney disease [77,78], and/or chronic obstructive pulmonary disease (COPD) [7981].…”
Section: Introductionmentioning
confidence: 99%
“…Inhaling H 2 S prior to myocardial ischemia at concentrations that had no metabolic depressant eff ect (10 ppm) attenuated organ damage, but to a lesser degree than concentrations that reduced energy expenditure (100 ppm) [12], suggesting that hypometabolism may indeed enhance the organ-protective properties of H 2 S. Of note, in that study as well as in others demonstrating H 2 S-related organ production coinciding with reduced metabolic activity, hypothermia was prevented [5], [7], [9], [14], [15] in order to elucidate the impact of a simultaneous drop in core temperature. Moreover, organ protection and improved survival were also shown to be in part [12], [13], [15], [34], [35] or even completely [8], [11], [36], [37] independent of any H 2 Sinduced metabolic depression at all. Finally, data obtained in large animal (swine or sheep) models of shock resulting from ischemia/reperfusion [29], [38]- [42], hemorrhage and resuscitation [30], or burn injury [36] also suggested that the benefi cial eff ects of infusing Na 2 S were at least in part independent of metabolic depression and/or a fall in core temperature.…”
Section: Hypothermiamentioning
confidence: 96%
“…Moreover, organ protection and improved survival were also shown to be in part [12], [13], [15], [34], [35] or even completely [8], [11], [36], [37] independent of any H 2 Sinduced metabolic depression at all. Finally, data obtained in large animal (swine or sheep) models of shock resulting from ischemia/reperfusion [29], [38]- [42], hemorrhage and resuscitation [30], or burn injury [36] also suggested that the benefi cial eff ects of infusing Na 2 S were at least in part independent of metabolic depression and/or a fall in core temperature. Hence, any moderate hypothermia observed simultaneously with H 2 S-induced organ-protection may also be due to attenuation of systemic infl ammation rather than to reduced energy expenditure per se.…”
Section: Hypothermiamentioning
confidence: 96%